Adopsi Pelanggan Terhadap Sistem Pembayaran Digital di Destinasi Wisata Yogyakarta Berdasarkan Perceived Usefulness, Trust, Perceived Ease of Use - Pradiatiningtyas, Diah; Dewa, Chriswardana Bayu; Safitri, Lina Ayu (Jurnal Ilmiah Pariwisata, 2023)
The Ministry of Tourism has designated go digital as the Ministry's Top 1 Program. Digital is an inevitable necessity and facts show that through digital everything can be done quickly. Tourism marketing and promotion now 50 to 70% use digital mechanisms. the author considers it necessary to discuss changes in consumer patterns regarding digital payments in tourist destinations, namely Yogyakarta, because the city is one of the destinations that tourists are interested in. This study discusses the implementation of digital payments in Yogyakarta tourist destinations by looking at the relationship between perceived benefits, perceived ease of use, trust and adoption as boundaries. This research is a qualitative descriptive study. Where the author uses primary and secondary data. The result obtained is that digital payments are felt to be easier for tourists who are already familiar with this technology and the maximum benefits are felt by tourists who are used to cashless payments. In certain tourist locations, such as beaches, the benefits have not been felt by tourists because the implementation in the field has not been fully carried out, tourist sites such as the Zoo, Heha Sky View and the like have implemented digital payments with the visitor segment who are familiar with digital payments. Keywords: Digital Payment, Tourism, Adoption, Trust, Perceive Usefulness, Ease of Use